2019
DOI: 10.15252/embj.2019103365
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of translational stalling by inhibitory codon combinations and poly(A) tracts

Abstract: Inhibitory codon pairs and poly(A) tracts within the translated mRNA cause ribosome stalling and reduce protein output. The molecular mechanisms that drive these stalling events, however, are still unknown. Here, we use a combination of in vitro biochemistry, ribosome profiling, and cryo-EM to define molecular mechanisms that lead to these ribosome stalls. First, we use an in vitro reconstituted yeast translation system to demonstrate that inhibitory codon pairs slow elongation rates which are partially rescue… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 65 publications
(167 reference statements)
7
122
0
Order By: Relevance
“…We observed that polybasic sequences led to slower ribosome movement during translation and an increase in disome formation. However, we could not detect signatures of severe ribosome stalling, such as the presence of short (20-22 nt) mRNA fragments which indicates empty A site in ribosomes [39]. These data suggested that polybasic sequences of endogenous proteins do not lead to RQC complex activation.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…We observed that polybasic sequences led to slower ribosome movement during translation and an increase in disome formation. However, we could not detect signatures of severe ribosome stalling, such as the presence of short (20-22 nt) mRNA fragments which indicates empty A site in ribosomes [39]. These data suggested that polybasic sequences of endogenous proteins do not lead to RQC complex activation.…”
Section: Introductionmentioning
confidence: 55%
“…Recently, it was shown that ribosomes with open A sites produce shorter mRNA fragments (20-22 nucleotides) than ribosomes with occupied A sites, which produce the longer mRNA fragments (27)(28)(29) nucleotides) analyzed in Figure 3a [35]. Structural and biochemical evidence demonstrated that the electrostatic repulsion caused by the presence of a polybasic sequence inside the exit tunnel can decrease the binding efficiency of an incoming tRNA carrying an additional positively charged residue, leading to empty A site ribosome [25,39,68]. Since ribosomes with empty A-site are recognized by translation termination factors, the analysis of 20-22 fragments could more accurately reflect translation efficiency [39].…”
Section: Ribosome Profiling Of Endogenous Proteins With Polybasic Seqmentioning
confidence: 99%
See 1 more Smart Citation
“…To ease comparison of translational features between samples, we also generate differential heatmaps for each sample pair, where the normalized difference between counts at every position from each codon is displayed ( Figure 3B,C). As certain combinations of codons or amino acids can also affect ribosome dynamics (35,36), we additionally analyzed the ribosome protection associated with the presence of two and three codon combinations (and di/tripeptide) ( Figure 3D-E).…”
Section: Fivepseq Facilitates Reproducible Analysis Of 5´p Degradomementioning
confidence: 99%
“…In addition to single amino acids, specific arrangement of consecutive amino acids can also lead to ribosome stalls, as the neighboring amino acids affect peptide bond formation or modulate interactions in the ribosome exit tunnel (35). In other cases, specific codon motifs can change the mRNA conformation, interfering with the decoding process (36). To facilitate the exploration of this phenomenon, we generate an automatic report investigating two or three codon (or amino acids) combinations able to produce ribosome stalls.…”
Section: Codon-specific Ribosome Protection Patterns Upon Eif5a Deplementioning
confidence: 99%